2023
DOI: 10.3389/frobt.2023.1190387
|View full text |Cite
|
Sign up to set email alerts
|

A length-adjustable vacuum-powered artificial muscle for wearable physiotherapy assistance in infants

Abstract: Soft pneumatic artificial muscles are increasingly popular in the field of soft robotics due to their light-weight, complex motions, and safe interfacing with humans. In this paper, we present a Vacuum-Powered Artificial Muscle (VPAM) with an adjustable operating length that offers adaptability throughout its use, particularly in settings with variable workspaces. To achieve the adjustable operating length, we designed the VPAM with a modular structure consisting of cells that can be clipped in a collapsed sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The field of soft robotics has opened up new avenues to design and fabricate actuators, sensors, and mechanisms ( Yasa et al, 2023 ). During the last decade, various actuation principles (e.g., pneumatic ( Xavier et al, 2022 ), dielectric ( Gupta et al, 2019 ), magnetorheological ( Bastola et al, 2020 ), magnetic ( Kim and Zhao, 2022 )) have motivated the development of soft actuators for a myriad of applications, ranging from aerospace to physiatry ( Huaroto et al, 2019 ; Yoo et al, 2019 ; Gollob et al, 2023 ; O’Neill et al, 2023 ; Zhang et al, 2023a ). In particular, soft pneumatic actuators have been the gold standard for creating large stroke actuation.…”
Section: Introductionmentioning
confidence: 99%
“…The field of soft robotics has opened up new avenues to design and fabricate actuators, sensors, and mechanisms ( Yasa et al, 2023 ). During the last decade, various actuation principles (e.g., pneumatic ( Xavier et al, 2022 ), dielectric ( Gupta et al, 2019 ), magnetorheological ( Bastola et al, 2020 ), magnetic ( Kim and Zhao, 2022 )) have motivated the development of soft actuators for a myriad of applications, ranging from aerospace to physiatry ( Huaroto et al, 2019 ; Yoo et al, 2019 ; Gollob et al, 2023 ; O’Neill et al, 2023 ; Zhang et al, 2023a ). In particular, soft pneumatic actuators have been the gold standard for creating large stroke actuation.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, some research groups have focused their efforts on modifying the default motion of actuators through passive and active mechanisms, enabling mechanical programming after fabrication. However, these attempts are limited to manually change actuator’s length ( Gollob et al, 2022 ) or to modify the curvature radius in bending actuators such as replacing components of the soft pneumatic actuators as chambers ( Natividad et al, 2018 ), and reinforcements [flexible sleeves ( Galloway et al, 2013 ) and rigid shells ( Chen et al, 2017 )], as well as embedding smart materials as internal layers ( Firouzeh et al, 2015 ; Yoshida et al, 2018 ). A few studies have demonstrated promising results, creating multifunctional artificial muscles capable of producing omnidirectional bending ( Murali Babu et al, 2023 ), bending and pure contraction ( Lin et al, 2020 ) as well as 7 modes of operation ( Zhang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Last yet importantly, their scalability feature makes devices comprising fabricbased bellow type actuators resonate well with the inherent need for a device focused on infant populations to adapt to fast growth. Indeed, as the infant develops and gains strength, the number of cells of the actuators can also be adjusted to provide the appropriate level of assistance, ensuring customized and progressive training [18], [28].…”
Section: Introductionmentioning
confidence: 99%